Analysis of Dapagliflozin and Empagliflozin Prescribing Patterns Based on the Clinical Profiles of Patients with Type 2 Diabetes Mellitus at Pharmacy X, Bandung - Nadlira Dzakiah Hermawan; Rida Emelia (Greenation Publisher & Yayasan Global Research National, 2026)
Type 2 Diabetes Mellitus (T2DM) is a chronic disease with a prevalence that continues to increase annually worldwide. SGLT2 inhibitors such as dapagliflozin and empagliflozin not only effectively lower blood glucose levels but also provide cardioprotective and renoprotective benefits, as demonstrated in various clinical trials. This study aims to analyze the prescribing patterns of dapagliflozin and empagliflozin and their association with the clinical characteristics of T2DM patients at Pharmacy X in Bandung. This quantitative study with a descriptive observational design involved 60 patients selected through consecutive sampling. Data were collected through structured interviews via WhatsApp and prescription verification. Data analysis employed descriptive statistics and the Chi-Square test. The results showed that respondents were predominantly male (66.67%) and aged >65 years (41.67%). Prescribing patterns showed balanced use of dapagliflozin and empagliflozin (50.00% each), with monotherapy being the most common pattern (60.00%). The most frequent comorbidity was ASCVD (30.00%). The Chi-Square test revealed no significant association between age (p=0.96), gender (p=0.10), therapy pattern (p=0.71), or comorbidity profile (p=0.31) with the type of SGLT2 inhibitor prescribed. The study concludes that the selection of dapagliflozin or empagliflozin at Pharmacy X is not influenced by demographic characteristics or therapy patterns, but is rather determined by clinical considerations such as the patient’s cardiovascular and renal risk profile. Further studies with larger populations are needed to confirm these findings.